2010
DOI: 10.1007/s00449-010-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotreatment of acidic zinc- and copper-containing wastewater using ethanol-fed sulfidogenic anaerobic baffled reactor

Abstract: The treatment of acidic (pH 6.5-3), sulfate- (2-3 g/L), Zn- and Cu- (total metal 0-500 mg/L) containing wastewater was studied in a four-stage anaerobic baffled reactor (ABR) at 35 °C for 250 days. Ethanol was supplemented (COD/SO4(2-) = 0.67) as carbon and electron source for sulfate reducing bacteria. Sulfate reduction, COD oxidation and metal precipitation efficiencies were 70-92, 80-94 and >99%, respectively. The alkalinity produced from sulfidogenic ethanol oxidation increased the wastewater pH from 3.0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…During Period III, the sulfate removal rate of immobilized SRB‐microalgae beads increased slowly as a result of aging SRB and consumption of the fermentation product. Overall, it reached 72.03–73.58%, which was comparable with results from the literature . In particular, when S. obliquus was encapsulated in beads, the sulfate removal rate of SRB was highest.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…During Period III, the sulfate removal rate of immobilized SRB‐microalgae beads increased slowly as a result of aging SRB and consumption of the fermentation product. Overall, it reached 72.03–73.58%, which was comparable with results from the literature . In particular, when S. obliquus was encapsulated in beads, the sulfate removal rate of SRB was highest.…”
Section: Resultssupporting
confidence: 87%
“…Overall, it reached 72.03-73.58%, which was comparable with results from the literature. 42 In particular, when S. obliquus was encapsulated in beads, the sulfate removal rate of SRB was highest. The removal efficiency of Cu(II) contaminated waters by immobilized SRB-S. obliquus beads was studied in the following dynamic experiment.…”
Section: Comparison Of Sulfate Reduction Between Immobilized Srb-micrmentioning
confidence: 98%
“…According to Zhang [53], the maximum sulfate reduction rate for treating AMD with SRB immobilized particles is 2.67 g/(L•d). Sahinkaya [55] showed that the maximum sulfate reduction rate of sulfate is approximately 3 g/(L•d) in an anaerobic baffle reactor. In order to promote the combination of SRB and coal gangue, the wet mud at the foot of gangue piles was used as seed mud to enrich SRB.…”
Section: Repair Effect Of Columns 1-4 On Amd With Different Pollutionmentioning
confidence: 99%
“…According to Hwang [2], the indigenous SRB enriched in the soil samples of the mining area has the potential to remove heavy metals and sulfate from AMD, but the removal efficiency is lower than Desulfovibrio desulfuricans. Compared with the above studies [53,55], coal gangue, as a large amount of solid waste accumulated in mining areas, is used to treat AMD with SRB, which is easy to operate and obtain materials for, and has strong acid neutralization ability and high metal ions removal efficiency. In the experimental results, the removal percentage of Mn was significantly lower than that of Fe.…”
Section: Repair Effect Of Columns 1-4 On Amd With Different Pollutionmentioning
confidence: 99%
“…The reactor started with 5.5% sulfate reduction, 1.9% Mn removal and pH increased in 3 days operation without any lag period due the inoculation with active SRB biomass from an optimum batch experiment. The active SRB may have increased over time and the bacteria may have been adapted to the operating conditions [1][2]31]. The performance of a sulfate removal increased maximum to 23% in 9 days operation.…”
Section: Sulphate Reductions Mn Removals and Ph Values Of Effluent Omentioning
confidence: 99%